Removal of arsenic in groundwater from western Anatolia, Turkey using an electrocoagulation reactor with different types of iron anodes - Kobya, Mehmet; Dolaz, Mustafa; Ozaydin-Senol, Burcu; Goren, Aysegul Yagmur (Cell Press, 2022)
Electrocoagulation (EC) is a significantly efficient method for As removal from waters and received considerable attention recently. In this study, the natural groundwater (GW) samples containing As concentrations of GW-1: 538.8 mu g L-1, GW-2: 1132.1 mu g L-1, and GW-3: 52, 000 mu g L-1 were obtained from different provinces and treated by EC process using different iron anodes (plate, ball, and scrap). To achieve drinking water As standard (10 mu g L-1), the operational time, applied current, and As removal optimization for all anode types were studied. At applied current of 0.025 A, the As removal efficiency, EC time, and operating cost were > 99.9%, 180 min and 0.406 $ m(-3) for ball anodes, > 99.9%, 100 min and 0.0813 $ m(-3) for plate anodes, > 99.9%, 80 min and 0.0815 $ m(-3) for scrap anodes for GW-3, respectively. It was observed that as the As concentration in the GW increased, the EC time and operating cost increased. Overall, it was concluded that Fe scrap anodes are more advantageous than other types of anodes in terms of operating cost in EC reactor for As removal.
Keywords: Arsenic removal; Electrocoagulation; Groundwater; Ball anode; Scrap anode; Plate anode